A comparative investigation on the role and interaction of EsxA and EsxB in host immune response. (May 2021) - Yi, Yuanyang; Wang, Hanqing; Su, Lingling; Wang, Hao; Zhang, Baojiang; Su, Yan
Abstract: Staphylococcus aureus ( S. aureus) is a frequent and major cause of bovine mastitis; it poses a tremendous economic burden to dairy industries of numerous countries. Early-secretion antigen-6 secretion system (ESS) has been viewed as an essential virulence and pathogenic factor of S. aureus . EsxA and EsxB are small acidic proteins secreted by ESS and identified as potential T-cell antigens of S. aureus . Unlike those of Mycobacterium tuberculosis ( M. tuberculosis ), the EsxA and EsxB of S. aureus do not form a dimer. Instead, EsxA dimerizes with itself or EsaC. Therefore, the interaction of EsxA and EsxB remains incompletely understood. In this study, to explore their interactions, EsxA and EsxB were expressed and used for immunization, alone or in combination, of murine infection models. Both components can interact with each other. Through the analysis of the immune response by immunological method, EsxB could significantly enhance the EsxA-specific IgG2a antibody level and increase the proliferation proportion of CD8 + T cells. These results indicate that when vaccinated with EsxA, EsxB can play a critical role in stimulating T helper 1 immunity by activating IgG2a and CD8 + T cells. We further show that vaccination with the combination of EsxA and EsxB resulted in enhanced stimulation of TLR-4 and improved protection against S. aureus . The findings may help us better understand the role of EsxB in the virulence and pathogenesis of S. aureus. Highlights: EsxB could significantly enhance the EsxA-specific IgG2a antibody level. EsxB could increase the proliferation proportion of CD8 + T cells. Vaccination with the combination of EsxA and EsxB resulted in enhanced stimulation of TLR-4. Immunization with EsxA and EsxB resulted in improved protection against S. aureus .